2019
DOI: 10.1111/ajt.15200
|View full text |Cite
|
Sign up to set email alerts
|

Vascular bioengineering of scaffolds derived from human discarded transplant kidneys using human pluripotent stem cell–derived endothelium

Abstract: The bioengineering of a replacement kidney has been proposed as an approach to address the growing shortage of donor kidneys for the treatment of chronic kidney disease. One approach being investigated is the recellularization of kidney scaffolds. In this study, we present several key advances toward successful re‐endothelialization of whole kidney matrix scaffolds from both rodents and humans. Based on the presence of preserved glycosoaminoglycans within the decelullarized kidney scaffold, we show improved lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 23 publications
1
33
1
Order By: Relevance
“…Scaffolds have become a hope for clinical translation due to their features of biocompatibility, biochemical and biological cues for cell adhesion, proliferation, migration, differentiation, and continued function [78,79]. Renal scaffolds were successfully produced from porcine, rat, and human kidneys [80][81][82][83][84]. Considering as a potent cell source for scaffold recellularization, embryonic stem cells and adipose tissue-derived stem cells have been seeded into renal scaffolds, achieving cell adherence, proliferation, differentiation, endothelialization, and vascularization [84][85][86][87].…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scaffolds have become a hope for clinical translation due to their features of biocompatibility, biochemical and biological cues for cell adhesion, proliferation, migration, differentiation, and continued function [78,79]. Renal scaffolds were successfully produced from porcine, rat, and human kidneys [80][81][82][83][84]. Considering as a potent cell source for scaffold recellularization, embryonic stem cells and adipose tissue-derived stem cells have been seeded into renal scaffolds, achieving cell adherence, proliferation, differentiation, endothelialization, and vascularization [84][85][86][87].…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 99%
“…Renal scaffolds were successfully produced from porcine, rat, and human kidneys [80][81][82][83][84]. Considering as a potent cell source for scaffold recellularization, embryonic stem cells and adipose tissue-derived stem cells have been seeded into renal scaffolds, achieving cell adherence, proliferation, differentiation, endothelialization, and vascularization [84][85][86][87]. Du et al have first attempted to repopulate a kidney scaffold using hiPSC-derived endothelial cells (hiPSC-ECs) [88].…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 99%
“…Bonandrini et al . supplied these cells through renal artery at a concentration of 12 × 10 6 cells and dynamically perfused the scaffold with a recirculating medium for a maximum of 72 h. Adult‐derived iPSCs represent another inexhaustible but costly alternative . Abolbashiri et al .…”
Section: Kidneymentioning
confidence: 99%
“… isolated primary porcine renal cells to repopulate decellularized scaffolds and showed that these cells were capable of electrolyte absorption and erythropoietin production. Furthermore, endothelial cells have been used for the repopularization of the vascular tree in bioengineered kidneys to prevent the thrombosis of the otherwise exposed ECM . Song et al .…”
Section: Kidneymentioning
confidence: 99%
“…Endothelial cells were present in the cortex with expression levels comparable to normal human kidney. Moreover, hardly any occlusions where detected and the recellularized kidney was successfully perfused with blood [102]. Obviously, re-epithelialization with iPSC-derived renal epithelial cells would be the next step.…”
Section: Applicationsmentioning
confidence: 99%